2018
DOI: 10.1093/brain/awy051
|View full text |Cite
|
Sign up to set email alerts
|

PRRT2 controls neuronal excitability by negatively modulating Na+ channel 1.2/1.6 activity

Abstract: See Lerche (doi:) for a scientific commentary on this article. PRRT2 mutations cause heterogeneous paroxysmal neurological disorders. Using iPSC-derived neurons from patients homozygous for a nonsense PRRT2 mutation and cortical neurons from PRRT2-knockout mice, Fruscione et al. show that PRRT2 is a negative modulator of voltage-dependent NaV1.2/1.6 channels. Increased neuronal excitability may contribute to the paroxysmal nature of PRRT2-linked diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
125
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(137 citation statements)
references
References 51 publications
(80 reference statements)
12
125
0
Order By: Relevance
“…16 Given that attacks of PKD are suppressed by carbamazepine, the molecular mechanism of the attacks could involve transient hyperactivity of VGSCs due to the activity-dependent cleavage of PRRT2. 16 Given that attacks of PKD are suppressed by carbamazepine, the molecular mechanism of the attacks could involve transient hyperactivity of VGSCs due to the activity-dependent cleavage of PRRT2.…”
Section: Significance Of the Cleavage Of Prrt2 To 12k-ctfmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Given that attacks of PKD are suppressed by carbamazepine, the molecular mechanism of the attacks could involve transient hyperactivity of VGSCs due to the activity-dependent cleavage of PRRT2. 16 Given that attacks of PKD are suppressed by carbamazepine, the molecular mechanism of the attacks could involve transient hyperactivity of VGSCs due to the activity-dependent cleavage of PRRT2.…”
Section: Significance Of the Cleavage Of Prrt2 To 12k-ctfmentioning
confidence: 99%
“…Third, the cleavage might enhance the VGSC activities at the AIS, followed by greater action potentials through the transient retraction of the PRRT2 function negatively modulating Na V 1.2/1.6, subunits of VGSCs. 16 Given that attacks of PKD are suppressed by carbamazepine, the molecular mechanism of the attacks could involve transient hyperactivity of VGSCs due to the activity-dependent cleavage of PRRT2. Taken together, the three putative mechanisms mediated by the cleavage of PRRT2 might result in transient dysfunctions of PRRT2 and an activity-dependent enhancement of neuronal excitation.…”
Section: Significance Of the Cleavage Of Prrt2 To 12k-ctfmentioning
confidence: 99%
See 1 more Smart Citation
“…PRRT2 interacts with SNARE complex proteins SNAP‐25, STX1A and VAMP2, as well as Ca 2+ sensors Syt1/2, all of which are important regulators of synchronous neurotransmitter release at the pre‐synaptic terminal . A study in homozygous patient‐derived induced pluripotent stem cells revealed that PRRT2 also directly binds and negatively regulates voltage‐gated Na + channels Na v 1.2 and Na v 1.6, resulting in increased Na + currents in homozygous cells . In vitro knockdown in primary neurons results in synaptic defects; namely decreased synaptic contacts, reduced synchronous neurotransmitter release and an insensitivity to extracellular Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…13,17,18 A study in homozygous patient-derived induced pluripotent stem cells revealed that PRRT2 also directly binds and negatively regulates voltage-gated Na + channels Na v 1.2 and Na v 1.6, resulting in increased Na + currents in homozygous cells. 19 In vitro knockdown in primary neurons results in synaptic defects; namely decreased synaptic contacts, reduced synchronous neurotransmitter release and an insensitivity to extracellular Ca 2+ . 18 A role for PRRT2 in inhibition of vesicle fusion at the synapse has also been described.…”
Section: Introductionmentioning
confidence: 99%